An Improved Immune Clone Selection Algorithm for Palm Bio-impedance Spectroscopy - LinTao LV; QinQin Yuan; YuXiang Yang (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
A kind of effective feature model of palm BIS data is presented according to the features of Palm bio-impedance spectroscopy (BIS) data. Based on immune clone algorithm and least squares method, an improved palm BIS feature selection algorithm is established,which can be applied to obtain the optimal feature subset that can be completely represented the palm BIS data, Finally, the algorithm is compared with other algorithms. The experimental results show that the accuracy of the feature subset obtained by the algorithm has reached 93.2 in SVM classification algorithm test.Therefore, the algorithm in this article is valid and reliable , which is of high theoretical and practical value.